Land Use Planning: Conflict Management Tool in Pastoral Areas in Kenya - Kagema, Charles; Jadeed, Munira (International Livestock Research Institute, 2022)
Conflict Management Tool in Pastoral Areas in Kenya; A presentation by Charles Kagema and Munira Jadeed of the National Land Commission (Kenya) Directorate of Land Use Planning NAIROBI